Поняття та система принципів адміністративної діяльності міліції - Крепакова, М. Ю.; Kriepakova, M. Y.; ORCID: http://orcid.org/0000-0001-5705-5027 (Вісник Харківського національного університету внутрішніх справ. - 2014. - № 1 (64). - С. 121-129, 2014)
Визначено поняття принципів адміністративної діяльності міліції, розглянуто систему принципів адміністративної діяльності міліції в контексті сучасного праворозуміння. Наведено класифікацію кожного принципу адміністративної діяльності міліції за конкретними критеріями, приділено окрему увагу значенню принципів адміністративної діяльності міліції.

The problems of legal regulation of police administrative activity are observed in the article. The notion of principles of police administrative activity is determined, the system of principles of police administrative activity in the context of modern law understanding is observed. The point of principles of police administrative activity is clarified. Practically scientific researches of principles of police administrative activity were not specially conducted, although a lot of research papers are devoted to the problems of police administrative activity. Thus it’s time to develop the conception of principles of police administrative activity. This fact is confirmed by the wish of legislator to embody some fundamental regulations in legal acts. The classification of every principle of police administrative activity according to the specific criterion is made. Special attention is paid to the notion of principles of police administrative activity. The conception of principles of police administrative activity, which is confirmed by the wish of legislator to embody some fundamental regulations in legal acts, is developed. Examined principles create methodological base of police administrative activity, run through all its types, forms and methods. In addition to that the principles of police administrative activity require further scientific analysis, because proper functioning of the whole police system depends on the effectiveness of police administrative activity.

Определено понятие принципов административной деятельности милиции, рассмотрена система принципов административной деятельности милиции в контексте современного правопонимания. Представлена классификация каждого принципа административной деятельности милиции по конкретным критериям, уделено особое внимание значению принципов административной деятельности милиции.
Крєпакова, М. Ю. Поняття та система принципів адміністративної діяльності міліції / М. Ю. Крєпакова // Вісник Харківського національного університету внутрішніх справ. - 2014. - № 1 (64). - С. 121-129.
Keywords: Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Органи внутрішніх справ. Internal affairs agencies. Органы внутренних дел; Internal Affairs Agencies; органы внутренних дел; міліція; милиция; militia; адміністративна діяльність